Modos de aplicação de zinco na nutrição e na produção de matéria seca do milho BRS 1001 - Prado, Renato Mello [UNESP]; Romualdo, Liliane Maria; Rozane, Danilo Eduardo; Vidal, Anelisa de Aquino; Marcelo, Adolfo Valente (Universidade Federal de Uberlândia (UFU), 2008)
The culture of the maize is responsive the fertilization with zinc, however, its efficiency can be affected by the method of aplication. Thus, this work had as objective to evaluate the effect of the methods of zinc application in the nutritional state and the initial growth of the culture of the maize. The experiment was in a completely randomized design, with five treatments in four repetitions. The experimental unit was composed for a pot (7 L) filled with a distrofic Red Latosol, clayey texture, with four plants of maize. The treatments had been constituted by four ways of zinc application: in the soil incorporated (3 mg Zn dm(-3)), and located (1 mg Zn dm(-3)); foliar (solution of 23 mg Zn L(-1)); e in seed (40 g Zn kg(-1) of seed) and beyond the witness (control). The treatments had been applied during two cultivation of 42 days, except the Zn incorporated in the soil. In the end of each culture, the cut of the plants for the evaluation of the growth variable (leaf height, number, the diameter of stems and dry matter) and the determination of the zinc text was carried through in the soil and the aerial part. The zinc application promoted increment in the height and the production of matter of the maize. The zinc application soil (incorporated and located), foliar and seed had been similar in the initial development of the culture, however, the foliar way promoted greater absorption of the nutrient for the plant.

A cultura do milho é responsivo a adubação com zinco, entretanto, a sua eficiência pode ser afetada pelo modo de aplicação. Assim, este trabalho teve como objetivo avaliar os efeitos dos métodos de aplicação de zinco no estado nutricional e no crescimento inicial da cultura do milho. O delineamento experimental foi inteiramente casualizado, com cinco tratamentos em quatro repetições. A unidade experimental foi composta por um vaso (7 L) preenchido com um Latossolo Vermelho distrófico, textura argilosa, com quatro plantas de milho. Os tratamentos foram constituídos por quatro modos de aplicação de zinco: no solo incorporado (3 mg Zn dm-3), e localizado (1 mg Zn dm-3); foliar (solução de 23 mg Zn L-1); e nas sementes(40 g Zn kg-1 de semente) e além da testemunha (controle). Os tratamentos foram aplicados durante dois cultivos de 42 dias, exceto o Zn incorporado no solo. No final de cada cultivo, foi realizado o corte das plantas para a avaliação das variáveis de crescimento (altura, número de folhas, o diâmetro do caule e massa seca) e a determinação do teor de zinco no solo e na parte aérea. A aplicação de zinco promoveu incremento na altura e na produção de matéria do milho. A aplicação de zinco via solo (incorporado e localizado), foliar e semente foram semelhantes no desenvolvimento inicial da cultura, entretanto, a via foliar promoveu maior absorção do nutriente pela planta.
Method of zinc application in the nutrition and the production of dry matter of maize BRS 1001
Keywords: Micronutrient; Zea mays L.; Aplication foliar; Method of aplication